Short Communication Cationic Effect on the Electrolyte Flocculation of Cassava Starch Emulsion: Short Communication: Electrolyte Flocculation of Cassava Starch (Biological Sciences - PJSIR, 2010)
The study to investigate, whether cassava starch emulsions are prone to flocculation by electrolytes and the role of the cationic valency in the instability showed that the electrolyte treated samples exhibited various degree of creaming and increase in globule size which depended on the cationic valency of the electrolyte, whereas the untreated samples hardly exhibited any evidence of creaming or changes in globules structure after 24 h of preparation. The trivalent cationic electrolyte (FeCl3) gave the most pronounced effect, while the monovalent cationic electrolyte (NaCl) gave the least effect on the creaming and globule size increase indicating that the instability is associated with the adsorption of the cationic moiety of the electrolyte on the globules to neutralize anionic charges on the globules surfaces.